Cysteine‐Assisted Click‐Chemistry for Proximity‐Driven, Site‐Specific Acetylation of Histones. Issue 46 (18th October 2022) - Afonso, Cláudia F.; Marques, Marta C.; António, João P. M.; Cordeiro, Carlos; Gois, Pedro M. P.; Cal, Pedro M. S. D.; Bernardes, Gonçalo J. L.
Abstract: Post‐translational modifications of histones are essential in the regulation of chromatin structure and function. Among these modifications, lysine acetylation is one of the most established. Earlier studies relied on the use of chromatin containing heterogeneous mixtures of histones acetylated at multiple sites. Differentiating the individual contribution of single acetylation events towards chromatin regulation is thus of great relevance. However, it is difficult to access homogeneous samples of histones, with a single acetylation, in sufficient quantities for such studies. By engineering histone H3 with a cysteine in proximity of the lysine of interest, we demonstrate that conjugation with maleimide‐DBCO followed by a strain‐promoted alkyne‐azide cycloaddition reaction results in the acetylation of a single lysine in a controlled, site‐specific manner. The chemical precision offered by our click‐to‐acetylate approach will facilitate access to and the study of acetylated histones. Abstract : We present a proximity‐driven, lysine‐specific acetylation approach to construct precisely acetylated histone proteins. The approach is facilitated by a click reagent equipped with an acetate group donor to acetylate a nearby lysine in a sequence‐controlled manner.